Analysis of Continuity of Care in Pregnant Women on Newborn Weight, Immunization, and Postpartum Contraceptive Use in Jember District - Restiningsih, Restiningsih; Damayanti, Nyoman Anita; Armunanto, Armunanto (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Reducing the Maternal Mortality Rate (MMR) to <70 per 100,000 live births is a global SDG target. Despite a decline in maternal deaths, infant mortality in East Java remains high. The Geliat Airlangga–UNICEF program applies a Penta Helix approach through continuity of care to improve maternal and child health outcomes. Objective: To analyze the effect of continuity of care for pregnant women on newborn birth weight, immunization, and postpartum contraceptive use in Jember District. Method: This observational analytic study involved 100 pregnant women supported by volunteers from December 2024 to June 2025 in three health centers. Data were collected from logbooks and analyzed using the Spearman correlation test. Result and Discussion: Most respondents (90%) were aged 20–35 years, 70% were primigravida, and 86% had MUAC >23.5 cm. A weak positive correlation was found between support frequency and newborn birth weight (r=0.185; p<0.05). No significant correlation was found with immunization status (r=0.163; p>0.05), while a weak negative correlation existed with postpartum contraception (r=-0.227; p<0.05). Continuous support improved maternal awareness and early detection but had varied effects on postpartum practices. Conclusions: Continuity of care positively influences pregnancy readiness and newborn outcomes. Strengthening community-based, volunteer-supported maternal care can contribute to reducing maternal and infant mortality in Jember District.